Placental lncRNA Expression Is Associated With Prenatal Phthalate Exposure. (29th January 2018) - Machtinger, Ronit; Zhong, Jia; Mansur, Abdallah; Adir, Michal; Racowsky, Catherine; Hauser, Russ; Brennan, Kasey; Karlsson, Oskar; Baccarelli, Andrea A
Abstract: Phthalates are endocrine-disrupting chemicals that can cross the placenta and affect the fetal epigenome. Among various epigenetic regulators of gene expression, long noncoding RNAs (lncRNAs) are important players that may also be involved in the manifestation of endocrine-disrupting chemical toxicity. We sought to explore the association between maternal urinary phthalate metabolite concentrations and lncRNA expression in human placenta to better understand potential mechanisms through which lncRNAs participate in mediating phthalate toxicity. Ten patients with uncomplicated dichorionic diamniotic twin pregnancies at term were included in this study. Urinary ( n = 10) and placenta samples ( n = 20) were collected for all participants. Urinary samples were analyzed for 15 phthalate metabolites and 2 phthalate alternative metabolites. Real-time PCR arrays were used to identify and quantify 87 lncRNAs from the placental samples. We tested the Spearman correlation matrix to compare prenatal phthalate measures against placental lncRNA levels. lncRNA levels showed large variations across samples, with no significant differences in lncRNA expression within twin pairs. Mono-(carboxynonyl) phthalate demonstrated consistently strong correlations with most lncRNAs. The strongest correlation was observed between mono-hydroxyisobutyl phthalate and LOC91450 ( R spearman = 0.88, p < .001). This correlation remained significant after Bonferroni adjustment. Other strong correlations were observed between mono-isobutyl phthalate, DPP10 and HOTTIP ( R spearman = −0.91, p < .001). AIRN, DACT3.AS1, DLX6, DPP10, HOTTIP, LOC143666, and LOC91450 were strongly correlated with the greatest number of phthalate metabolites. Further studies are needed to validate these results and understand if the altered expression of lncRNAs in human placenta has clinical significance.